Simple Algorithms for Estimating the Symbol Timing Offset in DCT-Based Multicarrier Systems. (15th July 2018) - Cruz-Roldán, Fernando; Piñeiro-Ave, José; Rojo-Álvarez, José L.; Blanco-Velasco, Manuel
Abstract : Multicarrier modulation based on discrete cosine transform (DCT-MCM) is a candidate technique for future wireless communication. DCT-MCM provides a better usage of the spectrum, allowing for much lower out-of-band radiation than conventional OFDM. In this paper, we address the problem of correcting the symbol timing offset in DCT-MCM. Two sliding window-based correlation algorithms are proposed. The new approaches consider a prefix and a suffix that are inserted into each data symbol, which are the replica of part of the useful data. The performance of the proposed approaches is verified and tested, and their usefulness and effectiveness are illustrated by computer simulations.